Income Analysis Of Broiler Carcass’ Traders in Kupang City Traditional Market - Kamengmai, Maria Petronela; Ratu, Maria R.D.; Sogen, Johanes G.; Tiro, Melkianus; Sol’uf, Morin Mediviani (JURNAL ILMIAH PETERNAKAN TERPADU, 2024)
A survey in April 2023 was conducted on broiler chicken carcass’ traders in the Kupang City traditional market which aimed to: find out the income of broiler chicken carcass traders in the Kupang City traditional market. Sampling was carried out through two stages, namely the determination of four traditional markets purposively and the determination of carcass traders as respondents was carried out randomly non-proportionally so that 60 representative respondents were obtained. The data analysis used is revenue analysis. The data was processed using Microsoft Excel 2010. The results of the analysis show that the income of broiler chicken carcass traders in the traditional market of Kupang City is Rp14,698,832 / year or capital productivity in this business is 69.74%. In summary, it can be said that the broiler chicken carcass sales business has been able to generate income for broiler chicken carcass traders. So it is recommended that broiler chicken carcass traders in the traditional market of Kupang City can improve carcass quality management, promote the carcass produced to consumers, and expand marketing networks by using digital marketing through social media so that the business they run can provide greater profits.